Exploring University Teacher Perceptions About Out-of-Class Teamwork - Elizabeth Ruiz-Esparza Barajas; Cecilia Araceli Medrano Vela; Jesús Helbert Karim Zepeda Huerta (Profile Issues in Teachers' Professional Development, 2016)
This study reports on the first stage of a larger joint research project undertaken by five universities in Mexico to explore university teachers’ thinking about out-of-class teamwork. Data from interviews were analyzed using open and axial coding. Although results suggest a positive perception towards teamwork, the study unveiled important negative opinions. These opinions suggest the lack of success in promoting deep learning and in developing students’ socio-cognitive abilities. Findings were used to develop a survey to be applied to more teachers to gain a broader perspective and to corroborate results.